American Society Of Civil Engineers Hold Session In Engineering Societies' Building (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1917)
One session of the annual meeting of the American Society of Civil Engineers-the first since this society became a Founder society with representation on the Board of the United Engineering Society-was held on Jan. 17, 1917, in the Engineering Societies' Building. Mr. Charles F. Rand, Past-President of this Institute, and President of the United Engineering Society, welcomed the new Founder society in the following words: "As one who has looked forward very earnestly to this clay, and who has made a modest effort in favor of the new arrangements, it is a peculiar satisfaction to be the representative of the Trustees of the United Engineering Society and to welcome you on the occasion of your first meeting in this building in which you now own' a quarter interest. "'As this is your annual meeting, I cannot take your time for extended remarks, yet it seems proper that I should call attention to a few facts respecting the United Engineering Society, with which you are now identified. "The United Engineering Society exists for the purpose of holding the legal title to certain of the property of the societies of Civil, Mining, Mechanical and Electrical Engineers and to act for them in certain matters. "The value of its property, including real estate, the Library and the Reserve and Endowment funds, exceeds two million dollars, all free and clear. "The total membership of the four Founder societies is 29,000 and the membership of associate societies is 23,000, making a grand total of 52,000 engineers who now have headquarters in this building.